Risk factors for meticillin-resistant Staphylococcus aureus colonization in dialysis patients: a meta-analysis. Issue 3 (November 2015) - Karanika, S.; Zervou, F.N.; Zacharioudakis, I.M.; Paudel, S.; Mylonakis, E.
Summary Background Patients on dialysis are particularly vulnerable to meticillin-resistant Staphylococcus aureus (MRSA) infections and MRSA colonization is associated with increased risk for severe infections in this population. Aim Determination of risk factors for MRSA colonization among dialysis patients. Methods This is a systematic review and meta-analysis of studies reporting risk factors of MRSA colonization. We performed a PubMed and EMBASE literature search to identify all studies on risk factors for MRSA colonization among patients undergoing dialysis treatment. Previous hospitalization, type of dialysis access, comorbid conditions, dialysis vintage, gender, length of time on dialysis, and previous antibiotic use were extracted and assessed for possible association with MRSA colonization in this population. Findings Ten out of 8252 articles, presenting data on 2364 dialysis patients, were included. We found that hospitalization within the previous 12 months [odds ratio (OR): 1.93; 95% confidence interval (CI): 1.04–3.58] and the use of temporary dialysis access (relative risk: 1.66; 95% CI: 1.06–2.60) were associated with a significantly higher risk of MRSA colonization. MRSA carriage was associated with lower serum albumin levels compared to non-carriage (OR: 0.8; 95% CI: 0.68–0.95) and was higher among patients with chronic lung disease (OR: 2.16; 95% CI: 1.04–4.51). There were no data on patients undergoing peritoneal dialysis. Conclusion Active surveillance approaches, including potential decolonization strategies, are suggested to focus on these subgroups of haemodialysis patients with hospitalization within the previous year, temporary dialysis access, lower serum albumin levels, and chronic lung disease comorbidity.